Discriminación política en el campo laboral dentro de las entidades del estado peruano durante el periodo 2016-2018 - Reyes Ruiz, Rina del Pilar (2024)
Labor discrimination due to political ideology cannot be agreed, because we are talking about rights that are protected and established in our constitution and the international mechanisms approved by the Peruvian state. However, there are public institutions that violate the basic rights of citizens, discriminate against them in labor competitions and include them in their publications as one of the requirements for obtaining or applying for jobs, there are also political factions that once arrive those in power discriminate against applicants for employment in public institutions due to political ideology. In our results we find statistical evidence that verifies these facts, since individuals who are affiliated with a political party earn on average 3.7% more than non-affiliated and work 3.7% less than them, in the same way the results show us that individuals affiliated with political parties have a 5.8% greater probability of working in a public institution, these results are theoretically consistent and with the Peruvian reality.